2012
DOI: 10.1345/aph.1q383
|View full text |Cite
|
Sign up to set email alerts
|

Use of Topical Tranexamic Acid or Aminocaproic Acid to Prevent Bleeding After Major Surgical Procedures

Abstract: Topical application of tranexamic acid and aminocaproic acid to decrease postsurgical bleeding after major surgical procedures is a promising strategy. Further data are needed regarding the safety of this hemostatic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 68 publications
1
48
0
1
Order By: Relevance
“…9 It is widely used in different surgical procedures such as cardiac surgery, upper gastrointestinal bleeding and post-partum haemorrhage. [10][11][12][13] Multiple reports have shown the effectiveness of TXA to control bleeding in knee arthroplasty. [14][15][16][17] However, its route of administration is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…9 It is widely used in different surgical procedures such as cardiac surgery, upper gastrointestinal bleeding and post-partum haemorrhage. [10][11][12][13] Multiple reports have shown the effectiveness of TXA to control bleeding in knee arthroplasty. [14][15][16][17] However, its route of administration is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…The use of tranexamic acid in orthopedic surgery recently has been gaining favor due to its efficacy and ease of use, both in IV and topical usage. Cost, bioavailability, efficacy, and low complications have contributed to the increase in the administration of TXA in TKA [13]. However, some case reports have shown that IV tranexamic acid is associated with a higher rate of pulmonary embolisms [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Topical treatment is cost-effective, and adverse effects or drug interactions have not been reported. 8 There are several published clinical trials for the use of TXA in the obstetric setting as well, but no consensus on its use or guidelines for management. 7 In the view of limited, good-quality evidence is available to inform on the best practices for prevention of bleeding at caesarean section due to placenta previa.…”
mentioning
confidence: 99%